Lisabetta and Lorenzo's tomb (on Decameron IV,5) - Camboni, M (American Association of Teachers of Italian, 2017)
This paper suggests a new interpretation of the tale of Lisabetta da Messina (Decameron IV,5) in the light of a fact that has thus far been disregarded by scholars: namely, that in both medieval culture, and its basis in Roman law, an individual cannot have more than one grave. In case of dismemberment, the burial place corresponds to where the head is interred. Therefore, the pot of basil in Boccaccio's tale is Lorenzo's tomb, and Lisabetta beheads her dead lover in order to be able to perform suitable funeral rites. Taking this into account, her behaviour as well as other aspects of the tale take on new meanings.